PENGARUH SOCIAL MEDIA MARKETING PADA BRAND IMAGE DAN BRAND TRUST TERHADAP PURCHASE INTENTION PRODUK KOSMETIK SARIAYU MARTHA TILAAR (Studi kasus pada social media Instagram) - Syarfina Estiana Zahira; Adhi Prasetio (Departemen Manajemen, 2021)
The study is aimed at finding the effects of there any influence of social media marketing in brand image and brand trust and to find out the influence of brand trust and brand image on purchase intention of cosmetic products with the Sariayu Martha Tilaar brand through Instagram social media of that brand. The method used in this research is to collect data obtained from distributing questionnaires totaling 400 respondents including the Sariayu Martha Tilaar future consumers following the instagram account or those who have previously seen the commercials uploaded by the account. In analyzing the data using SEM analysis or Structural Equation Model assisted by SMARTPLS software. From the results of hypothesis testing that researchers have done, researchers found a positive influence between the two variables (social media marketing with brand trust and brand image) and brand trust also has a positive influence on purchase intention.